Analisis Kebutuhan Pengembangan Kompetensi Manajerial Melalui Penilaian Kompetensi Pada Jabatan Fungsional Tertentu Provinsi Sulawesi Selatan - Ana Fitriani; Pratiwi Halik (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2023)
A certain functional is one of the ASN that has a role in carrying out functional services based on certain expertise and skills. Managerial competence refers to the regulation of PANRB Number 38 of 2017 which states that every ASN is required to have 8 managerial competencies and 1 social-cultural. In addition, certain functional have the right to develop competencies at least 20JP/year, so entitled to receive the necessary training to improve their competencies. The purpose of this research is to identify appropriate training needs in improving certain functional competence. Data collection in this study was carried out by measuring through the assessment center method to assess the managerial competence. The data were then processed using descriptive statistical analysis. The number of participants was 157 people who came from certain functional positions within the Province of South Sulawesi. Based on the results of this study, it was found that all of the certain functional had not reached the competency standard in accordance with the specified requirements. It is expected that functional positions can develop their competencies by participating in training programs for optimize their competencies to complete the task.